Question

# 3x + 4y = -23 2y - x = -19 What is the solution (x, y) to the system of equations above? A) (-5,-2) B) (3, -8) C) (4, -6) D) (9,-6)

Answer

(31, -6)

- Q: What is the first step in solving a system of equations by substitution? A: Solve one of the equations for one variable in terms of the other.
- Q:Which equation should we solve for one variable in terms of the other? A: We will solve 2y - x = -19 for x.
- Q:What is the next step in solving a system of equations by substitution? A: Substitute the expression found in step 2 into the other equation and solve for the remaining variable.
- Q:Substituting the expression found in step 2 into 3x + 4y = -23, what do we get? A: 3(2y + 19) + 4y = -23.
- Q:Solving for y in the equation found in step 4, what do we get? A: y = -6.
- Q:Substituting y = -6 into the expression found in step 2, what do we get? A: 2(-6) - x = -19.
- Q:Solving for x in the equation found in step 6, what do we get? A: x = 31.